Candida Bezoars with Urinary Tract Obstruction in Two Women without Immunocompromising Conditions - Giuseppe Di Paola; Andrea Mogorovich; Girolamo Fiorini; Maria Giuseppa Cuttano; Francesca Manassero; Cesare Selli (The Scientific World Journal)
More than half of the cases of fungal infections of the urinary tract are caused by Candida sp., but occurrence of obstructive uropathy caused by mycetomas or fungus balls (urobezoars) is extremely rare. The latter are conglomerates of fungal hyphae. Diabetes mellitus, immunosuppression, chronic disease, and malignancies are known predisposing factors. Preoperative imaging is not pathognomonic; blood clots, radiolucent urinary calculi, air bubbles, and inflammatory debris can mimic urobezoars. We report on two otherwise healthy women presenting with urinary tract obstruction caused by candidal mycetomas of the renal pelvis that mimicked matrix lithiasis.